2021
DOI: 10.1002/glia.24090
|View full text |Cite
|
Sign up to set email alerts
|

Microglia modulate hippocampal synaptic transmission and sleep duration along the light/dark cycle

Abstract: Microglia, the brain's resident macrophages, actively contribute to the homeostasis of cerebral parenchyma by sensing neuronal activity and supporting synaptic remodeling and plasticity. While several studies demonstrated different roles for astrocytes in sleep, the contribution of microglia in the regulation of sleep/wake cycle and in the modulation of synaptic activity in the different day phases has not been deeply investigated. Using light as a zeitgeber cue, we studied the effects of microglial depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
48
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 85 publications
10
48
1
2
Order By: Relevance
“…Importantly, this work is the first to show canonical cycling genes maintain their diurnal expression patterns in the absence of microglia, suggesting microglia may not be key regulators of rhythmicity in the brain. These findings are consistent with a recent study showing no overt variations in diurnal and circadian motor activity patterns between control and PLX5622-treated mice 41 . Counter to this, a previous study concluded that microglial ablation disrupts the circadian system in Cx3cr1-diphtheria toxin rats 33 .…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, this work is the first to show canonical cycling genes maintain their diurnal expression patterns in the absence of microglia, suggesting microglia may not be key regulators of rhythmicity in the brain. These findings are consistent with a recent study showing no overt variations in diurnal and circadian motor activity patterns between control and PLX5622-treated mice 41 . Counter to this, a previous study concluded that microglial ablation disrupts the circadian system in Cx3cr1-diphtheria toxin rats 33 .…”
Section: Discussionsupporting
confidence: 93%
“…Microglia contribute to downscaling during sleep by eliminating excitatory synapses (Choudhury et al, 2019), a behaviour presumably tuned down during wake by noradrenaline (Liu et al, 2019; Stowell et al, 2019). More recently, microglial CX3CR1 signalling was shown to differentially regulate excitatory synaptic transmission along the light/dark cycle (Corsi et al, 2021). We now show that microglia tune a sleep/wake regulation of inhibitory synapses restricted to cortical layer 1, via mobilization of the P2RX7/TNFα signalling and regulation of synaptic GABA A R content.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the latter, such as prostaglandin, BDNF, IL- 1β or TNFα, control synaptic plasticity and were independently shown to regulate sleep (Porkka-Heiskanen, 2013). Recent work highlights the ability of microglia to control sleep duration (Corsi et al, 2021; Liu et al, 2021); however, whether and how microglia-released factors shape sleep via modulation of synaptic plasticity remains unknown.…”
mentioning
confidence: 99%
“…TNFα is a signaling molecule known to control activation of phosphorylation pathways (15)(16)(17). In the brain, TNFα is mostly if not exclusively produced by microglia (18,19), which are active sensors of brain state (20)(21)(22) and have been recently proposed to participate in the regulation of sleep (23)(24)(25). We therefore hypothesized that microglia-derived TNFα is involved in phosphorylation-based control of sleep.…”
Section: Introductionmentioning
confidence: 99%